Dialecticisms as a Source of Literary Language Enrichment - Khodjayeva, Dilnoza Shavkatovna; Khusanov, Eldar Davletovich (International Journal of Formal Education, 2024)
Dialects are important resources in the enrichment and development of literary language in different system languages. In some languages sheva and lahja( they are Uzbek words) are called dialectics, and in others they are called language variants. In this article, the authors scientifically compare the terms of some linguistic dialects found in the Uzbek language in different systematic languages, namely English and Uzbek, with their English counterparts, and try to prove that dialectal words are the main factor in the development of any language. . The differences between literary language and other forms of language are also explained.